Dynamics of Multicultural Communication at Dayah MUDI, Mesjid Raya Samalanga - Mahyuddin, Mulyadi (Institut Agama Islam Al-Aziziyah Samalanga, 2024)
This study discusses multicultural communication at Dayah MUDI Mesjid Raya Samalanga, Bireuen Regency, Aceh Province. Although discussions with similar themes have often been encountered, the facts demand that discussions about this continue to be explored so that multicultural communication in Islamic boarding schools and the like can run well. Because so far, no appropriate concept has been found to overcome obstacles to multicultural communication. Clashes often occur in educational institutions, which lead to abuse and even death. The purpose of this study is to analyze how multicultural communication between students at Dayah MUDI Mesjid Raya Samalanga works. This study uses a qualitative research type with an ethnographic method that is descriptive analysis. Data collection techniques are carried out through observation, interviews, and documentation. The results of the study show that Dayah MUDI Mesjid Raya Samalanga has special characteristics in managing multicultural communication, namely by creating special dormitories, designing educational rooms, designing adaptive classes, creating weekly religious studies with caregivers, and creating private lessons. There are two obstacles: stereotypes and ethnocentrism. In the face of ethnocentrism, students tend to joke rather than be serious.